Association between tea consumption and risk of cancer: a prospective cohort study of 0.5 million Chinese adults - Li, Xinyi (Eur J Epidemiol, 2019)
Current experimental and epidemiological studies provide inconsistent evidence toward the association between tea consumption and cancer incidence. We investigated whether tea consumption was associated with the incidence of all cancers and six leading types of cancer (lung cancer, stomach cancer, colorectal cancer, liver cancer, female breast cancer and cervix uteri cancer) among 455,981 participants aged 30–79 years in the prospective cohort China Kadoorie Biobank. Tea consumption was assessed at baseline (2004–2008) with an interviewer-administered questionnaire. Cancer cases were identified by linkage to the national health insurance system. Cox proportional hazard regression models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). In the present population, daily tea consumers were more likely to be current smokers and daily alcohol consumers. 22,652 incident cancers occurred during 10.1 years follow-up (5.04 cases/1000 person-years). When we restricted analyses to non-smokers and non-excessive alcohol consumers to minimize confounding, tea consumption was not associated with all cancers (daily consumers who added tea leaves > 4.0 g/day vs. less-than-weekly consumers: HR, 1.03; 95%CI, 0.93–1.13), lung cancer (HR, 1.08; CI, 0.84–1.40), colorectal cancer (HR, 1.08; CI, 0.81–1.45) and liver cancer (HR, 1.08; CI, 0.75–1.55), yet might be associated with increased risk of stomach cancer (HR, 1.46; CI, 1.07–1.99). In both less-than-daily and daily tea consumers, all cancer risk increased with the amount of tobacco smoked or alcohol consumed. Our findings suggest tea consumption may not provide preventive effect against cancer incidence. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10654-019-00530-5) contains supplementary material, which is available to authorized users.